Empirical Study On Factors Determining E-Business Usage On Business Performance In Malaysian Service Industry - Mohamed, Intan Salwani (2010)
E-Business usage has become a significant research area since the Internet became prominent just over a decade ago. Many researchers have studied and proposed theories and models of E-business usage and value creations in order to predict and explain a company\'s technology investment. Each theory or model has been proposed with different sets of determinants and moderators and most of them have been developed in advanced countries such as the United States (U.S.). It was therefore questioned whether the theories and models related to E-business technology investment that have been developed, modified, and extended in the advanced countries are relevant to developing countries such as Malaysia.